Ur gonna have to pick an equation and solve for a variable.
2x - 2y = 6
2x = 2y + 6 ...divide everything by 2 because u want x by itself
x = y + 3
now we sub y + 3 in for x in the other equation
14x - 2y = 78
14(y + 3) - 2y = 78...distribute thru the parenthesis
14y + 42 - 2y = 78...subtract 42 from both sides, cancelling the 42 on the left
-42 -42
-----------------------
14y - 2y = 36 ...simplify
12y = 36...divide by 12 on both sides, cancelling out the 12 on the left
y = 36/12
y = 3
now , we already know that x = y + 3...and we know y = 3...so sub in 3 for y and solve for x
x = y + 3
x = 3 + 3
x = 6
solution is (6,3)
it is always a good idea to check ur answer by subbing it into one or both of the equations to see if it is correct
2x - 2y = 6......(6,3)...x = 6 and y = 3
2(6) - 2(3) = 6
12 - 6 = 6
6 = 6 (correct)
so yes, ur solution is (6,3)
Formula: A = 2wl + 2lh + 2hw
So... : A = 2(4x8) + 2(8x3) + 2(3x4)
A = 2(32) + 2(24) + 2(12)
A = 64 + 48 + 24
<u>Answer: A = 136</u> (add them all up)
Hope this helps!!!
:)
Answer:
it ix 23 then 43
Step-by-step explanation:
<h2>
Answer:</h2><h2>
g = 2 and h = -5</h2>
Step-by-step explanation:
To find the product with unknown values of variables, multiply the terms and equate the value to the given product.
= ![21d^{4} + 7hd^{3} - 56d^{2} - 9d^{3} - 3hd^{2} + 24d + 3gd^{2} + ghd - 8g](https://tex.z-dn.net/?f=21d%5E%7B4%7D%20%20%2B%207hd%5E%7B3%7D%20-%2056d%5E%7B2%7D%20-%209d%5E%7B3%7D%20-%203hd%5E%7B2%7D%20%2B%2024d%20%2B%203gd%5E%7B2%7D%20%2B%20ghd%20-%208g)
=
... (1)
Comparing eq(1) to the product given in question,
-8g = -1
g = 2
24 + gh = 14, sub g =2,
24 + 2h = 14
h = -5